2022
DOI: 10.1039/d1dt03471e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in externally controlled ring-opening polymerisations

Abstract: Switchable catalysis is a powerful tool in the polymer chemist’s toolbox as it allows on demand access to a variety of polymer architectures. Switchable catalysts operate by the generation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Most of the reported catalysts exhibited decreased catalytic activity or even complete deactivation at high temperatures or high monomer feed ratios owing to the decomposition of the active species. [9][10][11][12][13][14][15][16][17][18][19] Based on these considerations, we further evaluated the thermostability and protic impurity tolerance for salen-Al/PPNCl and (BpyBph)-Al/PPNCl binary catalysts with a [LA] : [catalyst pair] feed ratio of 500 : 1 (Tables 2 and 3). The catalytic activities of 1/PPNCl, 2/PPNCl and 5/PPNCl increased to some extent by elevating the polymerization temperature from 80 to 130 °C (entries 1-6, Table 2).…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reported catalysts exhibited decreased catalytic activity or even complete deactivation at high temperatures or high monomer feed ratios owing to the decomposition of the active species. [9][10][11][12][13][14][15][16][17][18][19] Based on these considerations, we further evaluated the thermostability and protic impurity tolerance for salen-Al/PPNCl and (BpyBph)-Al/PPNCl binary catalysts with a [LA] : [catalyst pair] feed ratio of 500 : 1 (Tables 2 and 3). The catalytic activities of 1/PPNCl, 2/PPNCl and 5/PPNCl increased to some extent by elevating the polymerization temperature from 80 to 130 °C (entries 1-6, Table 2).…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…One important objective of contemporary research is to develop catalysts that exhibit sufficient thermal stability under industrially relevant conditions, and can achieve fast polymerization rate and high molar mass polyester at a low catalyst loading. Many catalytic systems, including organometallics, [9][10][11][12][13][14][15][16][17][18][19] organocatalysts [20][21][22][23][24][25] and Lewis pairs, [26][27][28][29][30][31][32][33] have been developed over the past few decades. Organometallics are one class of versatile catalytic systems for ROP, because their catalytic performance can be easily modulated by tuning the Lewis acidity of the metal centre and modifying the electronic or steric effects of the ligand backbone.…”
Section: Introductionmentioning
confidence: 99%
“…27 Recently, block co-polyesters have been achieved by a chemoselective switch catalysis between the ring opening copolymerization of epoxides and anhydrides and the ROP of lactones or macrolactones. 28,29…”
Section: Introductionmentioning
confidence: 99%
“…27 Recently, block copolyesters have been achieved by a chemoselective switch catalysis between the ring opening copolymerization of epoxides and anhydrides and the ROP of lactones or macrolactones. 28,29 Generally, the most investigated catalysts for the ROP of cyclic esters and for the ROCOP of epoxides and anhydrides are heteroleptic complexes of non-toxic metals such as magnesium [30][31][32] and zinc, [33][34][35] in which the metal center is coordinated to electronically and sterically tailored ancillary ligands and labile ligand/s that often behave as initiating groups; while this strategy offers the benefits of a very efficient control over polymerization behavior (such as tacticity), [36][37][38] its disadvantages include somewhat less sustainable nature of the catalyst because of the required multistep synthesis of ancillary ligands. In contrast, recent studies have demonstrated that simple metal-alkoxides or metal-amides, which are commonly used as metal precursors in coordination chemistry, may represent a more sustainable route for polyester synthesis [39][40][41][42][43][44] and/or their degradation by alcoholysis.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent developments adapted the photoinitiation strategy to more sophisticated processes including: visible light promoted initiation, 5,6 cationic polymerizations, 7 controlled radical polymerizations (e.g. ATRP, RAFT), [8][9][10] ring-opening polymerizations (ROP), 11,12 and high resolution multiphoton fabrication methods. [13][14][15][16] As the demand for the synthesis of increasingly sophisticated polymeric materials rises, the need for new methods of controlled polymerization processes also increases.…”
Section: Introductionmentioning
confidence: 99%